Fractional PDª control of an hexapod robot - Silva, Manuel (2019)
This paper studies the performance of a Fractional Order PDª controller in a hexapod robot with three dof legs and leg joint actuators having saturation. For that objective the robot prescribed motion is characterized in terms of several locomotion variables. Moreover, two indices measure the walking performance based on the mean absolute density of energy per travelled distance and on the hip trajectory errors. A set of simulation experiments reveals the influence of the different controller tuning upon the proposed indices.